Peran Kepemimpinan Kepala Sekolah Dalam Meningkatkan Kedisiplinan Guru: - Elastari Matondang, Silvia (Jurusan Teknik Sipil, Politeknik Negeri Ketapang, 2024)
Education is a process of forming students' personalities which is based on the values of educators who are believed to be true. The process of education at school running well certainly requires qualified, disciplined teaching staff who have good personalities to be imitated by students. And teaching staff need guidance from a leader or principal in the school. This research aims to find out the role of the principal's leadership in improving teacher discipline at SDN 2020221 Silnadit school. This research was also carried out by conducting direct research in the field by meeting the school principal and his staff. The results of this research aim to find out how the principal implements leadership in the school